2023
DOI: 10.1002/ehf2.14332
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure with reduced ejection fraction and atrial fibrillation: a Sub‐Saharan African perspective

Abstract: Cardiovascular diseases are a well‐established cause of death in high‐income countries. In the last 20 years, Sub‐Saharan Africa (SSA) has seen one of the sharpest increases in cardiovascular disease‐related mortality, superseding that of infectious diseases, including HIV/AIDS, in South Africa. This increase is evidenced by a growing burden of heart failure and atrial fibrillation (AF) risk factors. AF is a common comorbidity of heart failure with reduced ejection fraction (HFrEF), which predisposes to an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 140 publications
(410 reference statements)
0
1
0
Order By: Relevance
“…For example in Sub-Saharan African, the incidence of previously rare forms of cardiovascular diseases, such as coronary artery disease, is increasing, in concert with historically prevalent forms of disease, such as rheumatic heart disease that are yet to be optimally eradicated. 1 In Asia, the evidence on the risk factors for incident HF was limited in the past. Now, the Circulatory Risk in Communities Study, involving 5335 Japanese, showed that high body mass index, systolic blood pressure, diastolic blood pressure, diabetes current smokers emerged as important contributors.…”
Section: Epidemiology Of Heart Failurementioning
confidence: 99%
“…For example in Sub-Saharan African, the incidence of previously rare forms of cardiovascular diseases, such as coronary artery disease, is increasing, in concert with historically prevalent forms of disease, such as rheumatic heart disease that are yet to be optimally eradicated. 1 In Asia, the evidence on the risk factors for incident HF was limited in the past. Now, the Circulatory Risk in Communities Study, involving 5335 Japanese, showed that high body mass index, systolic blood pressure, diastolic blood pressure, diabetes current smokers emerged as important contributors.…”
Section: Epidemiology Of Heart Failurementioning
confidence: 99%